Iron‐Catalyzed and Air‐Mediated C(sp3)−H Phosphorylation of 1, 3‐Dicarbonyl Compounds Involving C−C Bond Cleavage. Issue 24 (4th November 2020) - Ou, Yingcong; Huang, Yuanting; Liu, Yu; Huo, Yanping; Gao, Yang; Li, Xianwei; Chen, Qian
Abstract: A C( sp 3 )−H phosphorylation has been achieved via the iron‐catalyzed cross‐coupling reactions between 1, 3‐dicarbonyl compounds and P(O)−H compounds involving C−C bond cleavages with air as the oxidant. This transformation provides a straightforward way to construct C( sp 3 )−P bonds, leading to the formation of β‐ketophosphine oxides in up to 93% yield with good functional group tolerance. Abstract :